The Effect of a Computerized Early Intervention Program on Developing Language Skills for Children with Disabilities - AlQawod, Ghada Awwad; Al-Dababneh, Kholoud Adeeb (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to identify the impact of a computerized early intervention program in developing language skills in children with disabilities, through developing a computerized early intervention program to develop language skills in children with disabilities and measure to monitor the impact of the program in developing these skills. Methodology: The study used a single-case study design, as it is the most suitable approach for the study’s topic. The children’s languge skills were measured pre-, post- and follow-up using the study tool (the scale) and they were trained on the study tool (the program), which was applied to the study sample consisting of 5 children with disabilities (autism spectrum, intellectual disability) aged (4-6) years who were enrolled in Al-Zarqa Comprehensive Centre for Integrated Day Services. Then, data for the study sample was collected and analyzed to reach results that help answer the research question. Results: The study's findings revealed statistically significant differences in the overall score between the pre-measurement and post-measurement of the scale, indicating that the computerized early intervention program improved language skills in children with disabilities. The results also revealed no statistically significant differences in the overall score between the scale's post-measurement and follow-up measurements, indicating that the program's effect on language skills in children with disabilities in the study sample remained stable. Conclusion: The study recommends strengthening early intervention programs with technology and assistive techniques, and computer software for children with disabilities because of their role in developing their language skills, increasing their level of concentration, and providing the immediate feedback they need to continue the educational process.